Fluvial transport of lead, zinc and copper contents in polluted mining regions - Corsi, A. C.; Landim, PMB (Springer, 2002)
Ore mines installed in the lower-middle portion of Ribeira de Iguape River (São Paulo State, southeastern Brazil), together with the Panelas Plant are responsible for the contamination of the Iguape-Cananeia-Paranagua lagoon-estuarine complex. The lower-middle portion of Grande Creek Basin, located in the district of Adrianopolis (Parana State, southern Brazil) is under environmental impact because of mining activities. The mines of Perau, at Perau Creek, Canoas at Canoas Creek, and Barrinha at Barrinha Creek and Laranjal Creek have been paralyzed. The transport of lead in fluvial sediments is mainly associated with organic matter, carbonates, the residual fraction, and adsorbables, whereas the transport of zinc is associated with the organic and residual fraction, oxides and hydroxides of iron and manganese, carbonate, and adsorbables. The transport of copper is associated with the residual fraction and oxides and hydroxides of iron and manganese, organic matter, carbonate, and adsorbables.
Keywords: contamination; fluvial sediments; lead; zinc; copper; São Paulo State; southeastern Brazil